Implications of E-Banking on Household Financial Management - Nuhasanah, Nuhasanah; Nugraha, Hendri Adi (Benefit: Journal of Bussiness, Economics, and Finance, 2023)
Financial management is carried out for small businesses as well as for major corporations, including digital financial services for consumers. As a result, it has an impact on how consumers use financial technology. Understanding behavioral changes in home finance management is the goal of this study. This study employed a qualitative methodology. Primary research data in the form of a questionnaire was used. Samples were collected from Pekalongan City homes. The study's findings indicated that because m-banking makes it so simple to conduct transactions, housewives who continue to keep track of their household's financial statements prefer to use banks when making deposits.